Stimuli Responsive, Programmable DNA Nanodevices for Biomedical Applications - Singh, Udisha; Morya, Vinod; Datta, Bhaskar; Ghoroi, Chinmay; Bhatia, Dhiraj (Frontiers in Chemistry, 2021)
The use of dynamic DNA nanotechnology has many potentials in both fundamental and applied science. The stimuli-responsive motifs, structural flexibility, and molecular programmability of DNA make it ideal for stimulus-responsive future nanodevices. We take stock of the recent progress of this fast-growing sub-area of DNA nanotechnology. We discuss different stimuli, motifs, scaffolds, and mechanisms of stimulus-responsive behaviors of DNA nanodevices with appropriate examples. Also, we present a multitude of biological applications that have been explored using DNA nanodevices, such as biosensing, in vivo pH mapping, drug delivery, and therapeutics. The present work concludes by discussing the challenges and opportunities, and prospects of this emerging research area within DNA nanotechnology.